Studi Penerapan Cara Produksi Pangan Yang Baik (CPPB) dan Umur Simpan Mi Glosor Di Kota Bogor - Soeka, Yati; Jumiono, Aji (Jurnal Ilmiah Pangan Halal, 2019)
One of the fast food sold by small and medium businesses is noodles. Noodles are preferred by consumers because they are cheap, affordable for all levels of society, can be processed into a variety of cuisines, and can be served quickly. One of the most common culinary noodles consumed by the people of Bogor city and its surroundings is the glutinous noodles which are widely served with various variations. However, in buying, sometimes people do not know whether the glossy noodles they consume are suitable foods to consume. This research aims to know the making of glossy noodles by the glossy noodles maker in Bogor city, based on good food production methods so that we can know the shelf life of glossy noodles in the laboratory by analyzing the total plate count and organoleptic test with packaging technique of HDPE plastic bags stored for 5 days, heat-resistant HDPE plastic sealed stored for 10 days and heat-resistant HDPE plastic which was vacuum stored for 15 days with no dyeing and with immersion treatments in water of 100 oC for 1 minute. Data on good food production methods is obtained by means of surveys that reveal case studies of a problem with a qualitative approach. The results of research showed that the results of observation of small and medium business in CV Taruna have four major activities, namely procurement of materials, production process, packaging, and marketing or delivering. Small and medium businesses of CV Taruna have 37 process flows. The conditions of implementing good food production methods are currently at level 4. The number of serious nonconformities of 3 elements and critical mismatches of 2 elements. The results of the analysis of the total plate numbers with packaging technique of HDPE plastic bags stored for 5 days, heat-resistant HDPE plastic sealed stored for 10 days and heat-resistant HDPE plastic which was vacuum stored for 15 days with no dyeing treatment and with immersion in water of 100 oC for 1 minute meet SNI requirements < 1x10-6 at room temperature for 72 hours. The results of organoleptic test with packaging technique of HDPE plastic bags stored for 5 days, heat-resistant HDPE plastic sealed stored for 10 days and heat-resistant HDPE plastic which was vacuum stored for 15 days with no dyeing treatment and with immersion in water of 100 oC for 1 minute for color, aroma, texture, and appearance on the score from dislike to very like. Keywords: small and medium enterprises, gloss noodles, shelf life, total plate count, organoleptic test.